The Diagnosis of Nostalgia from Teffi - Федотов, Олег (Acta Universitatis Lodziensis. Folia Litteraria Rossica, 2022)
The literature of the Russian diaspora, as one of the brightest national literatures created outside the metropolis, received an unprecedented acute sense of nostalgia as the most effective stimulus for its development. It permeates the works of virtually all Russian writers who, by the will of fate, found themselves abroad. The article examines nostalgic experiences in the work of the writer Nadezhda Teffi, extremely popular among Russian and foreign readers alike, on the basis of her prose novel Nostalgia (1920), a short story written before emigration in 1915 – “Tosca moja, tosca! Ja vizhu v den’ dozhdlivyj…” as well as a cycle of seven poems dedicated to the same topic in volume 3 of the Collected Works under the generalised title Tosca (in the first newspaper publication – Nostalgia). All the analysed texts follow the same strategy of describing the symptoms of unbearable homesickness, which Teffi adopted in an early poem of 1915 and developed in works written five years later in exile: the prose novel Nostalgia and the report of seven poems of 1920. An example of such a lyroepic polyphony for her could be Nikolay Nekrasov’s poem Sovremenniki, with one, albeit a significant, difference: in Nekrasov, each new character is endowed with an individual metric voice, while in Teffi, on the contrary, almost all nostalgic compatriots express their feelings in a universal verse.